2015
DOI: 10.1186/s13019-015-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect analysis of repeat sternotomy in pediatric cardiac operations

Abstract: BackgroundReoperation for congenital heart disease may be associated with cardiac or vascular injuries during repeat sternotomy, resulting in increased mortality and/or morbidity rates. The aim of this study was to determine the frequency of these cardiac injuries and the associated outcome.MethodsBetween January 2012 and December 2013, 4256 sternotomy procedures were performed at the Pediatric Cardiac Center in Fuwai Hospital, including 195 repeat sternotomy procedures (RS). We retrospectively studied the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…These findings were echoed in 2015 by Yin et al who demonstrated that while CPB time, skin incision to CPB time, ventilation time, cross-clamp time, and blood requirement were all significantly different between primary and redo sternotomies, there was no significant difference in mortality or morbidity. 2 This is consistent with our patient's outcome having an ischemic time of over four hours (258 minutes) and leaving the hospital without complications. At our institution, it is not standard practice to perform 3D imaging of the chest prior to re-sternotomy, though in this patient's case, many imaging studies were available.…”
Section: Commentsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings were echoed in 2015 by Yin et al who demonstrated that while CPB time, skin incision to CPB time, ventilation time, cross-clamp time, and blood requirement were all significantly different between primary and redo sternotomies, there was no significant difference in mortality or morbidity. 2 This is consistent with our patient's outcome having an ischemic time of over four hours (258 minutes) and leaving the hospital without complications. At our institution, it is not standard practice to perform 3D imaging of the chest prior to re-sternotomy, though in this patient's case, many imaging studies were available.…”
Section: Commentsupporting
confidence: 90%
“…In the pediatric literature, there is strong evidence that in the current era repeat sternotomy is not a risk factor for morbidity or mortality. 1,2 For example, Morales et al studied the incidence of injury and mortality during repeat sternotomy and found no significant difference in occurrence of injury or mortality between primary and redo sternotomies in a series of 602 repeat sternotomies performed in 558 patients. 1 In that series, rates of nonemergent blood transfusion, femoral cannulation, sternal wound infection, and reoperation for postoperative bleeding were all ≤1% with a 98% survival to discharge.…”
Section: Commentmentioning
confidence: 99%
“…Our recent study demonstrated that the risk of major bleeding during resternotomies was 1.8% in 108 patients. 1 Yin et al 6 reported 3.6% major injury during sternal reentry among 195 patients. Our primary choice for peripheral cannulation was femoral vessels.…”
Section: Commentmentioning
confidence: 99%
“…Nonetheless, in the last 20 years, this idea has been studied. [2][3][4] One of the first studies on the subject was carried out by Russell et al in 1998, with the conclusion that repeat sternotomy carries minimal added risk. 5 In 2008, Morales et al demonstrated that repeat sternotomy represents a negligible risk of injury and therefore that the choice of management strategies should not be affected by the need of a reoperation.…”
Section: Introductionmentioning
confidence: 99%